Blends of NR with EPDM waste devulcanized by microwave : mechanical properties and self healing ability / Nurain Najwa Che Rahim - Che Rahim, Nurain Najwa Che Rahim (2020)
The development in rubber industry may have serious impact on the earth which the increasing of rubber volume has become a huge waste. It is difficult to deal waste rubber as it cannot recycle easily to turn into new product. The devulcanization by microwave process can break apart the crosslink network and could reduce the Ethylene-Propylene-Diene Monomer (EPDM) waste. The Natural Rubber (NR) blends with EPDM waste with different accelerator/sulphur ratio (A/S = 0.2, 1, 4). The EPDM waste was grind into small pieces and blend with natural rubber. The compounding process is prepared by two-roll mill at room temperature. The cure time, tensile properties, hardness, abrasion resistance, FTIR analysis and self-healing ability of rubber blends were tested. The results obtained from blending of NR with M-EPDMA shows an increasing in tensile strength which is 3.9 MPa, tensile strain is 108.26%, swelling test 108.69%, decrease in hardness of 50.4. abrasion resistance index of 240.07 and Young Modulus value is 6.4. The formation of sulphur-sulphur (S-S) give 831.99 cm-1 showed the existence of chain break during microwave process and formation of peak at the N=C=S bond 2114.07 cm-1 assign that present only in the M-EPDM A because it had the lowest A/S ratio. Self-healing ability of the rubber showed the changes depending on the accelerator/sulphur ratio.